Dziadkowie jako znaczący inni w biograficznym doświadczeniu parentyfikacji - Chojnacka, Barbara (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
In modern societies, extended families are less frequent, while nuclear families are the norm, which is why narrow systems include parent-and-child subsystems. When disturbances and crises arise in such a structure, these situations are conducive to the mechanism of role reversal (parentification). It involves the system’s drawing from the resources available to it and thus transferring to children the responsibility and tasks that belong to adults. The subject of this study is a broader perception of the family taking into account its surroundings, especially grandparents. Based on the autobiographical narratives of individuals who experienced parentification in childhood, the reconstruction and analysis of their role as people of significance to their grandchildren was made. Grandparents supported their grandchildren, acted as guardians of the family, and ensured a sense of security, endowing parentified individuals with positive experiences and childhood memories.